Pemetaan Topografi Calon Lokasi Embung di Kampus IPB Darmaga, Bogor - Priyoadi, Bagus Rahmansyah; Setiawan, Budi Indra (Jurnal Teknik Sipil dan Lingkungan, 2020)
Before planning and designing a small dam, land’s topographic mapping and water flow pattern’s analysis are needed. The aim of this research were to identify the land use, water catchment areas, water flow pattern, and analyze land’s topographic condition, as well as producing topographic maps and calculating inundation volume at small dam location at IPB Campus Darmaga. This research was conducted in April - July 2019. The land use around the small dam location consisted of forests, roads, grasslands, bare land, settlements, and agriculture lands. The catchment area of the small dam location was divided into four area, with an area of 2881.0 m2, 4531.0 m2, 2790.0 m2, and 10917.3 m2 respectively. The highest and lowest elevations based on land measurements at small dam location were 199.71 masl and 187.23 masl. The topographic map was created using Surfer 13 software with the most appropriate interpolation method was natural neighbor. The direction of the surface water flow was relatively uniform and leads to the North and South. The minimum and maximum of inundation volume were 1.5 m3 and 13752.8 m3, and the optimum inundation volume was 2824.8 m3.